A Pattern of Tolerance Values Transformation by Parents Towards Early Childhood - Sumadi, Tjipto; Abdillah, Fauzi; Casmana, Asep Rudi (Frontiers in Education, 2021)
This study aims to discover a pattern of the transformation of tolerance values from parents to early childhood. The tolerance value in this day and age experiences some problems in the context of nationality. This can be seen from some parts of the area in Indonesia. For instance, in the traditional village of Cigugur, a life based on tolerance is experienced in the community. This study focused on the Cigugur community’s pattern of applying tolerance values in family and community life. This study uses a qualitative method to undertake the study. Observations and in-depth interviews were used to carry out the data collection, and then it was verified and validated through four stages: member check, audit trial, triangulation, and expert opinion. It can be concluded that the pattern of the transformation of tolerance values from parents to early childhood could be transformed through some stages; 1) making sense of kinship as an adhesive between followers of different religions, 2) conveying religious teachings towards differences, not to be contested but to be respected and admired, 3) avoiding the content of particular political interests, 4) having a sense compassion for each other, and 5) having tepo seliro (respect) for each other.